Dust collection plate for horizontal wet-type electric washing tower and preparation method of dust collection plate
By using a dust collecting plate composed of modified flame retardant resin and conductive fiber reinforced fiber reinforced layer, the problem of short service life of existing anode materials in high temperature and high corrosion environments is solved, and more efficient flue gas purification and longer service life are achieved.
Patent Information
- Application Number
- CN202510082120.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-20
AI Technical Summary
In existing wet electrostatic precipitators, the anode material has a short service life, poor acid resistance and poor conductivity in high-temperature and high corrosion environments, making it difficult to meet the needs of efficient flue gas purification.
The dust collecting plate for horizontal wet power scrubber tower consisting of a conductive fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced fiber reinforced
It significantly improves the acid resistance, conductivity and flame retardant properties of the dust collecting plate, extends the service life, and enhances the dust collection effect on pollutants in the flue gas.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to a dust collecting plate material, in particular to a dust collecting plate for a horizontal wet electric power washing tower and a preparation method thereof. Background Art
[0002] With the development of industries in various countries around the world, the expansion and reconstruction of power plants, steel mills, chemical plants, etc., and the exhaust of flue gas have become one of the important factors causing air pollution. As an advanced flue gas treatment technology, wet electrostatic precipitator technology has been widely used in Europe, the United States, Japan and other countries with good results. In recent years, with the upgrading of environmental protection standards, my country's research and application in the field of wet electrostatic precipitator has also made rapid progress. The carbon fiber conductive fiberglass anode tube that has emerged has occupied a place in this field with its excellent performance characteristics, and has been favored by many environmental protection design institutes and desulfurization and dust removal environmental protection companies.
[0003] As a highly efficient flue gas deep purification device, wet electrostatic precipitator can effectively remove acid mist, gypsum rain, heavy metal mercury, sol, etc. in flue gas. The anode tube plays a pivotal role in its internal components. Since the working conditions in this field are mostly saturated wet flue gas with a temperature of 50-80℃, the flue gas contains SO2, NOx, Cl - 、F - Compared with the commonly used anode tubes made of lead, hard PVC and other materials, carbon fiber conductive fiberglass has the characteristics of high strength, strong acid mist corrosion resistance, good rigidity, and not easy to deform. In addition, the use of carbon fiber and resin with good corrosion resistance and high flame retardancy makes the carbon fiber conductive fiberglass dust collecting plate an ideal material choice for the anode of the wet electrostatic precipitator.
[0004] According to the working conditions described above, the anode tube, as an important component of the dust collector, must meet the following performance requirements: strong corrosion resistance; good electrical conductivity; good flame retardant effect; high mechanical strength; good inner wall surface flatness and low operating water consumption; good dust collection effect; and long service life. Summary of the invention
[0005] Based on the application status of conductive glass fiber reinforced plastic anode tubes in the prior art, the present invention provides a dust collecting plate for a horizontal wet electric power washing tower and a preparation method thereof. The dust collecting plate is a conductive glass fiber reinforced plastic anode plate containing a special flame retardant resin.
[0006] First, the present invention provides a dust collecting plate for a horizontal wet electric power washing tower, which comprises a conductive anode plate composed of a plurality of conductive glass fiber reinforced plastic pipes arranged in a honeycomb shape, wherein the conductive glass fiber reinforced plastic pipes comprise inner and outer surface layers and a conductive glass fiber reinforced plastic layer located between the inner and outer surface layers; the inner and outer surface layers are carbon fiber surface felts, and the conductive glass fiber reinforced plastic layer is glass fiber felt and glass fiber coarse sand impregnated with modified flame retardant resin. In terms of weight percentage, the modified flame retardant resin comprises the following raw materials: 76-85% modified epoxy resin, 13-15% conductive filler, 2-2.5% curing agent, 0.7-1.1% non-cobalt accelerator and 3-5% diluent.
[0007] In some embodiments of the present invention, the preparation process of the modified epoxy resin comprises the following steps: S1: Add the catalyst and solvent into a reaction vessel, stir until completely dissolved, add vanillin and hydroxylamine hydrochloride, stir continuously and heat to 120-140°C, react for 3-5h; after the reaction is completed, cool to room temperature, dilute the reaction system with dichloromethane and extract with distilled water, remove the solvent from the obtained organic layer by rotary evaporation and dry to obtain intermediate product A; S2: Add intermediate product A and dichloromethane to another reaction container and stir until completely dissolved; under an ice bath, add trifluoromethanesulfonic acid dropwise to the reaction container, stir and mix evenly, then heat to 20-30°C and stir again for 10-12h; after the reaction is completed, pour the mixture into ice water, neutralize with ammonia solution, filter, wash with distilled water and dry to obtain intermediate product B; S3: Add the intermediate product B and the epoxy halide to another reaction container, stir until completely dissolved, heat the system to 70-80°C, add the ring-opening catalyst, and react at this temperature for 3-5 hours; after the reaction is completed, cool to 40-50°C, drop the strong alkali solution and continue to react for 3-5 hours; after the reaction is completed, naturally cool to room temperature, dilute with chloroform, extract with distilled water, and the obtained organic layer is rotary evaporated and dried to obtain a modified epoxy monomer; S4: dissolving the obtained modified epoxy monomer and epoxy resin in chloroform at a mass ratio of 5-7:3-5, adding a curing agent at a molar ratio of NH to epoxy group of 1:1, ultrasonicating for 30-40 minutes, stirring for 1-2 hours, and then volatilizing the solvent at 50-60°C, pouring into a glass mold, placing in an oven to fix the mold, performing post-hot pressing on a flat vulcanizer, cold pressing molding, and finally curing completely in an oven to obtain the modified epoxy resin.
[0008] Furthermore, the catalyst in S1 is at least one of anhydrous ferric chloride, anhydrous aluminum chloride, zinc dichloride and titanium tetrachloride; the usage mass accounts for 30-35% of the total mass of the vanillin and hydroxylamine hydrochloride; the solvent is at least one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, acetone, and ethylene glycol monomethyl ether.
[0009] Furthermore, the molar ratio of vanillin to hydroxylamine hydrochloride in S1 is 1:1-1.5.
[0010] Furthermore, the mass of the trifluoromethanesulfonic acid added in S2 is 3-3.5 times the mass of the intermediate product A.
[0011] Furthermore, the epichlorohydrin in S3 is at least one of epichlorohydrin, methyl epichlorohydrin, 2-(chloromethyl)-1,2-epoxybutane, 1,2-epoxychlorobutane, methyl epichlorobutane, 1,2-epoxychloropentane (CAS: 19141-74-3), and 1,1-dimethyl-1,2-epoxychloropentane (CAS: 408319-88-0).
[0012] Furthermore, the added mass of the epoxyhaloalkane in S3 is 5-6 times the mass of the intermediate product B.
[0013] Furthermore, the ring-opening catalyst in S3 is one of tetrabutylammonium bromide, ammonium chloride, ammonium hydrogen sulfate, trioctylmethylammonium chloride, and dodecyltrimethylammonium chloride, and the added mass is 2-3% of the total mass of the intermediate product B and the epoxyhaloalkane.
[0014] The preparation principle of the modified epoxy monomer described above is as shown in Formula I: , Formula I Wherein R is an alkylene oxide.
[0015] The method for preparing the dust collecting plate for the horizontal wet electric washing tower comprises the following steps: Step 1: Preparation of resin impregnation liquid: After the modified flame retardant resin is melted, a conductive filler, a non-cobalt accelerator, a curing agent and a diluent are sequentially added thereto to obtain a modified flame retardant resin impregnation liquid; wherein each time a component is added, it must be fully mixed with the modified epoxy resin before adding the next component; Step 2: Use hand lay-up process to coat the anode tube mold with 30g / m 2 The requirements of the carbon fiber surface felt are evenly coated with two layers, and then the carbon fiber surface felt is coated with 450g / m 2A layer of glass fiber felt and glass fiber coarse sand containing modified flame retardant resin is uniformly coated according to the requirements, and a conductive glass fiber reinforced plastic layer containing modified flame retardant resin is uniformly coated on the surface of the obtained conductive glass fiber reinforced plastic layer, and finally a layer of glass fiber chopped strand mat is formed to form an anode tube wall plate with a thickness of 1.8-2mm; Step 3: Assemble the dust collecting tube according to the use requirements to obtain the dust collecting plate.
[0016] Furthermore, in step three, when assembling the dust collecting pipes, first scrape a layer of a mixture of light powder, crushed glass fiber and modified flame retardant resin on the side of a single dust collecting pipe, and also scrape a layer on the side of another dust collecting pipe. Finally, the two dust collecting pipes are pressed tightly together, and the remaining dust collecting pipes are assembled in the same way, and finally assembled into several dust collecting pipes as a whole; among them, the last dust collecting pipe is assembled and hardened for 2 hours, and then left to stand for at least 2 hours.
[0017] Beneficial effects: Compared with the prior art, the present invention adds a fully bio-based triazine epoxy monomer prepared by using vanillin to the resin impregnated with the carbon fiber felt on the inner and outer surfaces of the dust collecting tube. The prepared modified flame-retardant resin contains triazine rings and benzene rings and has a strong polar NH, which is beneficial to improving the mechanical properties of the modified flame-retardant resin; in addition, the non-combustible gas generated by the modified flame-retardant resin when decomposed by heat can form a protective layer on the surface of the material, which can isolate the air to a certain extent, block the diffusion of oxygen to the surface of the material, and have a certain inhibitory effect on the thermal oxygen decomposition of the material; in addition, these non-combustible gases can dilute the concentration of flammable small molecules and oxygen after diffusing to the flame zone, and reduce the temperature of the flame zone to a certain extent, and the reduction in the temperature of the gas phase reaction zone is of great help to the reduction in the temperature of the condensed phase thermal decomposition zone, so that the modified flame-retardant resin has good self-extinguishing and heat resistance. Since there is no ester group on the modified flame retardant resin skeleton and both sides of the molecular chain are protected by alkyl groups, it exhibits good acid and alkali resistance; due to the certain electron carrier characteristics of the triazine ring and the conjugated structure of the benzene ring, the surface resistance of the dust collecting plate finally formed is less than 100Ω. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0019] The following is an exemplary description of the preparation process of the modified epoxy resin used in the embodiment:
[0020] Modified epoxy resin #1 S1: Add 6.65g of anhydrous ferric chloride and 100ml of DMF into a three-necked flask, stir until completely dissolved, then add 15.2g (0.1mol) of vanillin and 6.95g (0.1mol) of hydroxylamine hydrochloride, stir continuously and heat to 120°C, and react for 5h; after the reaction is completed, cool to room temperature, dilute the reaction system with dichloromethane and extract three times with distilled water, dry the obtained organic layer with sodium persulfate overnight, remove the solvent with rotary evaporation, and finally dry in a vacuum oven at 60°C overnight to obtain intermediate product A with a yield of 73.5%; S2: Add 16.0g of intermediate product A and 300ml of dichloromethane into another three-necked flask and stir until completely dissolved; under an ice bath, add 48.0g of trifluoromethanesulfonic acid dropwise into the reaction vessel, stir and mix evenly, then heat to 20°C and stir again for 12h; after the reaction is completed, pour the mixture into ice water, neutralize with 0.1mol / L ammonia solution, filter, wash three times with distilled water and dry to obtain intermediate product B with a yield of 60.5%; S3: Add 10.7g of intermediate product B and 53.5g of epichlorohydrin into another three-necked flask, stir until completely dissolved, heat the system to 70°C, add 1.28g of ring-opening catalyst tetrabutylammonium bromide, and react at this temperature for 5h; after the reaction is completed, cool to 40°C, add 30wt% NaOH solution (7.5g) dropwise and continue to react for 3h; after the reaction is completed, cool naturally to room temperature, dilute with chloroform, extract three times with distilled water, dry the obtained organic layer with anhydrous sodium sulfate overnight, filter and evaporate to remove epichlorohydrin and chloroform, and finally dry in a vacuum oven at 50°C overnight to obtain a modified epoxy monomer with a yield of 76.9%; S4: The obtained modified epoxy monomer and epoxy resin (915, purchased from Shanghai Shangwei Fine Chemical Co., Ltd.) were dissolved in chloroform at a mass ratio of 5:5, and the curing agent 4,4'-diaminodiphenylmethane was added at a molar ratio of NH to epoxy group of 1:1. Ultrasonic treatment was performed for 30 minutes and stirred for 1 hour. After the solvent was evaporated at 50°C, it was poured into a glass mold and placed in an oven for fixing and forming. Post-hot pressing and cold pressing were performed on a flat vulcanizer. Finally, it was completely cured in an oven to obtain the modified epoxy resin #1.
[0021] Modified epoxy resin #2 S1: Add 7.53g of anhydrous aluminum chloride and 100ml of N-methylpyrrolidone into a three-necked flask, stir until completely dissolved, then add 15.2g (0.1mol) of vanillin and 8.34g (0.12mol) of hydroxylamine hydrochloride, stir continuously and heat to 130°C for 4h; after the reaction is completed, cool to room temperature, dilute the reaction system with dichloromethane and extract three times with distilled water, dry the obtained organic layer with sodium persulfate overnight, remove the solvent with rotary evaporation, and finally dry in a vacuum oven at 60°C overnight to obtain intermediate product A with a yield of 71.7%; S2: Add 16.0g of intermediate product A and 300ml of dichloromethane into another three-necked flask and stir until completely dissolved; under an ice bath, add 51.2g of trifluoromethanesulfonic acid dropwise into the reaction vessel, stir and mix evenly, then heat to 25°C and stir again for 11h; after the reaction is completed, pour the mixture into ice water, neutralize with 0.1mol / L ammonia solution, filter, wash three times with distilled water and dry to obtain intermediate product B with a yield of 62.1%; S3: Add 21.7g of intermediate product B and 119.35g of 2-(chloromethyl)-1,2-butylene oxide into another three-necked flask, stir until completely dissolved, heat the system to 75°C, add 3.53g of ring-opening catalyst ammonium hydrogen sulfate, and react at this temperature for 4h; after the reaction is completed, cool to 45°C, add 35wt% NaOH solution (7.2g) dropwise and continue to react for 4h; after the reaction is completed, cool naturally to room temperature, dilute with chloroform, extract three times with distilled water, dry the obtained organic layer with anhydrous sodium sulfate overnight, filter and evaporate to remove epichlorohydrin and chloroform, and finally dry in a vacuum oven at 50°C overnight to obtain a modified epoxy monomer with a yield of 75.4%; S4: The obtained modified epoxy monomer and epoxy resin (915, purchased from Shanghai Shangwei Fine Chemical Co., Ltd.) were dissolved in chloroform at a mass ratio of 6:4, and the curing agent 4,4'-diaminodiphenylmethane was added at a molar ratio of NH to epoxy group of 1:1. Ultrasonic treatment was performed for 35 minutes and stirred for 1.5 hours. After the solvent was evaporated at 55°C, it was poured into a glass mold and placed in an oven for fixing and forming. Post-hot pressing and cold pressing were performed on a flat vulcanizer. Finally, it was completely cured in an oven to obtain the modified epoxy resin #2.
[0022] Modified Epoxy Resin #3 S1: Add 8.97g of anhydrous zinc dichloride and 100ml of ethylene glycol monomethyl ether into a three-necked flask, stir until completely dissolved, then add 15.2g (0.1mol) of vanillin and 10.43g (0.15mol) of hydroxylamine hydrochloride, stir continuously and heat to 140°C for 3h; after the reaction is completed, cool to room temperature, dilute the reaction system with dichloromethane and extract three times with distilled water, dry the obtained organic layer with sodium persulfate overnight, remove the solvent with rotary evaporation, and finally dry in a vacuum oven at 60°C overnight to obtain intermediate product A with a yield of 73.5%; S2: Add 16.0g of intermediate product A and 300ml of dichloromethane into another three-necked flask and stir until completely dissolved; under an ice bath, add 56g of trifluoromethanesulfonic acid dropwise into the reaction vessel, stir and mix evenly, then heat to 30°C and stir again for 10h; after the reaction is completed, pour the mixture into ice water, neutralize with 0.1mol / L ammonia solution, filter, wash three times with distilled water and dry to obtain intermediate product B with a yield of 65.3%; S3: Add 23.5g of intermediate product B and 141g of 1,2-epoxychloropropane into another three-necked flask, stir until completely dissolved, heat the system to 80°C, add 4.94g of ring-opening catalyst trioctylmethylammonium chloride, and react at this temperature for 3h; after the reaction is completed, cool to 50°C, add 40wt% NaOH solution (7.0g) dropwise, and continue to react for 5h; after the reaction is completed, cool naturally to room temperature, dilute with chloroform, extract three times with distilled water, dry the obtained organic layer with anhydrous sodium sulfate overnight, filter and evaporate to remove epichlorohydrin and chloroform, and finally dry in a vacuum oven at 50°C overnight to obtain a modified epoxy monomer with a yield of 72.6%; S4: The obtained modified epoxy monomer and epoxy resin (915, purchased from Shanghai Shangwei Fine Chemical Co., Ltd.) were dissolved in chloroform at a mass ratio of 7:3, and the curing agent 4,4'-diaminodiphenylmethane was added at a molar ratio of NH to epoxy group of 1:1. Ultrasonic treatment was performed for 40 minutes and stirred for 2 hours. After the solvent was evaporated at 60°C, it was poured into a glass mold and placed in an oven for fixing and forming. Post-hot pressing and cold pressing were performed on a flat vulcanizer. Finally, it was completely cured in an oven to obtain the modified epoxy resin #3.
[0023] Modified epoxy resin #4 Same as modified epoxy resin #3, except that the mass ratio of modified epoxy monomer to epoxy resin is 8:2.
[0024] The conductive filler used in the following examples is carbon powder (purchased from Shanghai Huigang Graphite Co., Ltd.), the non-cobalt accelerator used is 1305 and / or 1336 (purchased from Shangwei Shanghai Fine Chemical Co., Ltd.), the curing agent used is V388 (purchased from Akzo Nobel Chemical Co., Ltd.), the carbon fiber surface felt used is purchased from Kaifeng Pengyuan Glass Fiber Products Co., Ltd., the glass fiber chopped felt used is purchased from Shandong Taishan Glass Fiber Co., Ltd., and the diluent used is purchased from Changzhou Fuqiao Resin Co., Ltd.
[0025] Example 1 Step 1: Preparation of resin impregnation liquid: After 81.3% of modified epoxy resin #1 is melted, 13% of carbon powder, 0.7% of non-cobalt accelerator, 2% of curing agent and 5% of diluent are added thereto in sequence to obtain a modified flame retardant resin impregnation liquid; wherein each component must be fully mixed with the modified epoxy resin before adding the next component; Step 2: Use hand lay-up process to coat the anode tube mold with 30g / m 2 The requirements of the carbon fiber surface felt are evenly coated with two layers, and then the carbon fiber surface felt is coated with 450g / m 2 A layer of glass fiber felt and glass fiber coarse sand containing modified flame retardant resin is uniformly coated on the surface of the conductive glass fiber reinforced plastic layer; a layer of glass fiber chopped strand mat is uniformly coated on the surface of the conductive glass fiber reinforced plastic layer, and finally a 1.8 mm thick anode tube wall plate is formed; Step 3: Assemble the dust collecting tubes according to the use requirements. When assembling the dust collecting tubes, first scrape a layer of a mixture of light powder, crushed glass fiber and modified flame retardant resin on the side of a single dust collecting tube, and also scrape a layer on the side of another dust collecting tube. Finally, press the two dust collecting tubes tightly and assemble the remaining dust collecting tubes in the same way. Finally, assemble several dust collecting tubes as a whole. Among them, after the last dust collecting tube is assembled and hardened for 2 hours, it is left to stand for at least 2 hours to obtain the dust collecting plate.
[0026] Example 2 Step 1: Preparation of resin impregnation liquid: After 78.8% of modified epoxy resin #2 is melted, 14% of carbon powder, 1% of non-cobalt accelerator, 2.3% of curing agent and 4% of diluent are added thereto in sequence to obtain a modified flame retardant resin impregnation liquid; wherein each component must be fully mixed with the modified epoxy resin before adding the next component; Step 2: Use hand lay-up process to coat the anode tube mold with 30g / m 2 The requirements of the carbon fiber surface felt are evenly coated with two layers, and then the carbon fiber surface felt is coated with 450g / m 2A layer of glass fiber felt and glass fiber coarse sand containing modified flame retardant resin is uniformly coated according to the requirements, and a conductive glass fiber reinforced plastic layer containing modified flame retardant resin is uniformly coated on the surface of the obtained conductive glass fiber reinforced plastic layer, and finally a layer of glass fiber chopped strand mat is formed to form an anode tube wall plate with a thickness of 1.9 mm; Step 3: Assemble the dust collecting tubes according to the use requirements. When assembling the dust collecting tubes, first scrape a layer of a mixture of light powder, crushed glass fiber and modified flame retardant resin on the side of a single dust collecting tube, and also scrape a layer on the side of another dust collecting tube. Finally, press the two dust collecting tubes tightly and assemble the remaining dust collecting tubes in the same way. Finally, assemble several dust collecting tubes as a whole. Among them, after the last dust collecting tube is assembled and hardened for 2 hours, it is left to stand for at least 2 hours to obtain the dust collecting plate.
[0027] Example 3 Step 1: Preparation of resin impregnation liquid: After 78.4% modified epoxy resin #3 is melted, 15% carbon powder, 1.1% non-cobalt accelerator, 2.5% curing agent and 3% diluent are added thereto in sequence to obtain a modified flame retardant resin impregnation liquid; wherein each component must be fully mixed with the modified epoxy resin before adding the next component; Step 2: Use hand lay-up process to coat the anode tube mold with 30g / m 2 The requirements of the carbon fiber surface felt are evenly coated with two layers, and then the carbon fiber surface felt is coated with 450g / m 2 A layer of glass fiber felt and glass fiber coarse sand containing modified flame retardant resin is uniformly coated according to the requirements, and a conductive glass fiber reinforced plastic layer containing modified flame retardant resin is uniformly coated on the surface of the obtained conductive glass fiber reinforced plastic layer, and finally a layer of glass fiber chopped strand mat is formed to form an anode tube wall plate with a thickness of 2.0 mm; Step 3: Assemble the dust collecting tubes according to the use requirements. When assembling the dust collecting tubes, first scrape a layer of a mixture of light powder, crushed glass fiber and modified flame retardant resin on the side of a single dust collecting tube, and also scrape a layer on the side of another dust collecting tube. Finally, press the two dust collecting tubes tightly and assemble the remaining dust collecting tubes in the same way. Finally, assemble several dust collecting tubes as a whole. Among them, after the last dust collecting tube is assembled and hardened for 2 hours, it is left to stand for at least 2 hours to obtain the dust collecting plate.
[0028] Example 4 Same as Example 3, except that modified epoxy resin #3 is replaced by modified epoxy resin #4.
[0029] Comparative Example 1 Same as Example 3, except that epoxy resin (915, purchased from Shanghai Shangwei Fine Chemical Co., Ltd.) is used to replace modified epoxy resin #3.
[0030] Among them, in the above embodiments and comparative examples, when assembling a single dust collecting tube, first clean the mold, then put the stacked dust collecting tube into the mold (the dust collecting tube specification is 2*2*2*2), and the dust collecting tube specification can be selected according to the actual situation (the thickness should be selected to be pressed together), and 2 cm is cut off on one side of the broken tube. Tie it tightly to the mold with a strap and a wooden square, and make 2 layers of carbon fiber + 1 layer of glass fiber at the broken part, and finish it after hardening.
[0031] When the dust collecting pipe is assembled, fill the broken position with broken glass fiber + resin, and smooth the surface after hardening. This process takes about 6 hours. After it is completely hardened, use 2 cranes to lift the dust collecting pipe, fill the lower corner with resin and broken glass fiber, and smooth it after hardening. At this point, all dust collecting pipes are assembled.
[0032] The thickness after assembly is 5-6mm, the roughness of the inner surface is less than Ra12.5, and the roughness of the outer surface is less than Ra100.
[0033] Performance Testing Surface resistance: detected using AMC72-DI / MC embedded DC ammeter; Barcol hardness: measured according to GB / T3854-2005; Resin heat deformation temperature: measured in accordance with GB / T1634.3-2004; Tensile strength: measured in accordance with GB / T1447-2005; Bending strength: measured in accordance with GB / T1449-2005; Oxygen index: measured in accordance with GB / T8924-2005.
[0034] The test results are detailed in Table 1: Table 1 Test results of the dust collecting plates or their surface resins obtained in Examples 1-4 and Comparative Example 1
[0035] It can be seen from the data in Table 1 that when the mass ratio of the modified epoxy monomer to the epoxy resin in the modified epoxy resin is changed (exceeding the range of 5-7:3-5), the heat deformation temperature, mechanical properties and flame retardancy of the modified flame retardant resin obtained will not increase, but will be slightly weakened; when the modified epoxy monomer is not added to prepare the modified flame retardant resin, the various properties of the obtained resin are reduced, which shows the importance of the modified epoxy monomer for improving the resin performance on the surface of the dust collecting plate.
Claims
1. A dust collecting plate for a horizontal wet electric washing tower, comprising a conductive anode plate composed of a plurality of conductive glass fiber reinforced plastic pipes arranged in a honeycomb shape, wherein the conductive glass fiber reinforced plastic pipes include an inner surface layer, an outer surface layer and a conductive glass fiber reinforced plastic layer located between the inner surface layer and the outer surface layer; characterized in that: The inner and outer surface layers are carbon fiber surface felts impregnated with modified flame retardant resin. The modified flame retardant resin contains the following raw materials by weight: 76-85% modified epoxy resin, 13-15% conductive filler, 2-2.5% curing agent, 0.7-1.1% non-cobalt accelerator and 3-5% diluent.
2. The dust collecting plate for a horizontal wet electric washing tower according to claim 1, characterized in that: The preparation process of the modified epoxy resin comprises the following steps: S1: Add the catalyst and solvent into a reaction vessel, stir until completely dissolved, add vanillin and hydroxylamine hydrochloride, stir continuously and heat to 120-140°C, react for 3-5h; after the reaction is completed, cool to room temperature, dilute the reaction system with dichloromethane and extract with distilled water, remove the solvent from the obtained organic layer by rotary evaporation and dry to obtain intermediate product A; S2: Add intermediate product A and dichloromethane to another reaction container and stir until completely dissolved; under an ice bath, add trifluoromethanesulfonic acid dropwise to the reaction container, stir and mix evenly, then heat to 20-30°C and stir again for 10-12h; after the reaction is completed, pour the mixture into ice water, neutralize with ammonia solution, filter, wash with distilled water and dry to obtain intermediate product B; S3: Add the intermediate product B and the epoxy halide to another reaction container, stir until completely dissolved, heat the system to 70-80°C, add the ring-opening catalyst, and react at this temperature for 3-5 hours; after the reaction is completed, cool to 40-50°C, drop the strong alkali solution and continue to react for 3-5 hours; after the reaction is completed, naturally cool to room temperature, dilute with chloroform, extract with distilled water, and the obtained organic layer is rotary evaporated and dried to obtain a modified epoxy monomer; S4: dissolving the obtained modified epoxy monomer and epoxy resin in chloroform at a mass ratio of 5-7:3-5, adding a curing agent at a molar ratio of NH to epoxy group of 1:1, ultrasonicating for 30-40 minutes, stirring for 1-2 hours, and then volatilizing the solvent at 50-60°C, pouring into a glass mold, placing in an oven to fix the mold, performing post-hot pressing on a flat vulcanizer, cold pressing molding, and finally curing completely in an oven to obtain the modified epoxy resin.
3. The dust collecting plate for a horizontal wet electric washing tower according to claim 2, characterized in that: The catalyst in S1 is at least one of anhydrous ferric chloride, anhydrous aluminum chloride, zinc dichloride and titanium tetrachloride; the used mass accounts for 30-35% of the total mass of the vanillin and hydroxylamine hydrochloride; the solvent is at least one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, acetone, and ethylene glycol monomethyl ether.
4. The dust collecting plate for a horizontal wet electric washing tower according to claim 2, characterized in that: The molar ratio of vanillin to hydroxylamine hydrochloride in S1 is 1:1-1.
5.
5. The dust collecting plate for a horizontal wet electric washing tower according to claim 2, characterized in that: The mass of trifluoromethanesulfonic acid added in S2 is 3-3.5 times the mass of the intermediate product A.
6. The dust collecting plate for a horizontal wet electric washing tower according to claim 2, characterized in that: The epoxyhaloalkane in S3 is at least one of epichlorohydrin, methyl epichlorohydrin, 2-(chloromethyl)-1,2-epoxybutane, 1,2-epoxychlorobutane, methyl epichlorobutane, 1,2-epoxychloropentane, and 1,1-dimethyl-1,2-epoxychloropentane.
7. The dust collecting plate for a horizontal wet electric washing tower according to claim 2, characterized in that: The added mass of the epoxyhaloalkane in S3 is 5-6 times the mass of the intermediate product B.
8. The dust collecting plate for a horizontal wet electric washing tower according to claim 2, characterized in that: The ring-opening catalyst in S3 is one of tetrabutylammonium bromide, ammonium chloride, ammonium hydrogen sulfate, trioctylmethylammonium chloride, and dodecyltrimethylammonium chloride, and the added mass is 2-3% of the total mass of the intermediate product B and the epoxyhaloalkane.
9. The method for preparing the dust collecting plate for a horizontal wet electric power washing tower according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Preparation of resin impregnation liquid: After the modified epoxy resin is melted, a conductive filler, a non-cobalt accelerator, a curing agent and a diluent are sequentially added thereto to obtain a modified flame retardant resin impregnation liquid; wherein each time a component is added, it must be fully mixed with the modified epoxy resin before adding the next component; Step 2: Use hand lay-up process to coat the anode tube mold with 30g / m 2 The requirements of the carbon fiber surface felt are evenly coated with two layers, and then the carbon fiber surface felt is coated with 450g / m 2 A layer of glass fiber felt and glass fiber coarse sand containing modified flame retardant resin is uniformly coated according to the requirements, and a conductive glass fiber reinforced plastic layer containing modified flame retardant resin is uniformly coated on the surface of the obtained conductive glass fiber reinforced plastic layer, and finally a layer of glass fiber chopped strand mat is formed to form an anode tube wall plate with a thickness of 1.8-2mm; Step 3: Assemble the dust collecting tube according to the use requirements to obtain the dust collecting plate.
10. The method for preparing the dust collecting plate for a horizontal wet electric washing tower according to claim 9, characterized in that: In step three, when assembling the dust collecting pipes, first scrape a layer of a mixture of light powder, crushed glass fiber and modified flame retardant resin on the side of a single dust collecting pipe, and also scrape a layer on the side of another dust collecting pipe. Finally, press the two dust collecting pipes tightly together, and assemble the remaining dust collecting pipes in the same way. Finally, assemble several dust collecting pipes as a whole; among them, the last dust collecting pipe is assembled and hardened for 2 hours, and then left to stand for at least 2 hours.
Citation Information
Patent Citations
Conductive fiberglass reinforced polyester anode tube and preparation method thereof
CN102989587A
Anode of wet electrical dust precipitator
CN104707731A
Honeycomb-shaped bamboo plywood wet type electric precipitator anode
CN104759351A
Wet electric dust collector anode
CN105903569A
Titanium electrode ionization tube for wet electric dust collector
CN105944838A